2011
DOI: 10.1177/1474651411412429
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of type 2 diabetes by lifestyle intervention in primary health care setting in Poland: Diabetes in Europe Prevention using Lifestyle, physical Activity and Nutritional intervention (DE-PLAN) project

Abstract: AimTo find out whether diabetes prevention via a lifestyle intervention programme is feasible in a primary healthcare setting in Poland. MethodsThe intervention (Diabetes in Europe: Prevention using Lifestyle, physical Activity and Nutritional intervention; DE-PLAN project) was completed by 175 middle-aged, slightly obese participants in nine primary healthcare centres in Krakow, Poland. The inclusion criterion was diabetes risk (Finnish Diabetes Risk score (FRS) >14). The nurse-delivered intervention consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(49 citation statements)
references
References 24 publications
1
48
0
Order By: Relevance
“…We calculated the mean change by subtracting the baseline mean value from the mean at 12 months. We calculated the SD from reported P values or CI, as recommended by the Cochrane Collaboration (29). Where data were insufficient, to allow calculation of the SD, we imputed values for each outcome based on the correlation estimates from those studies that reported; for weight, the correlation used in these imputations was 0.95 (30-34).…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…We calculated the mean change by subtracting the baseline mean value from the mean at 12 months. We calculated the SD from reported P values or CI, as recommended by the Cochrane Collaboration (29). Where data were insufficient, to allow calculation of the SD, we imputed values for each outcome based on the correlation estimates from those studies that reported; for weight, the correlation used in these imputations was 0.95 (30-34).…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
“…Additional analysis comparing the difference in weight lost Gilis-Januszewska 2011 69 Ruggerio 2011 88 Kramer 2012 (CPC) 81 Kramer 2012 (TPC) 81 Laatikainen 2012 93 Kanaya et al 94 and Penn et al 95 ) have been added; therefore, the subtotal line and overall line in the plots have changed, as they now include additional data. Boxes and horizontal lines represent mean weight change and 95% CI for each study.…”
Section: Meta-analysismentioning
confidence: 99%
“…This is most likely to be a result of the fact that the WHO began recommending the use of HbA 1c as a T2DM diagnostic tool only in 2011, whereas many studies in this review predate this introduction. 50,62,[69][70][71][72][73][74][75][76][77][78][79][80]82,[85][86][87]89,96,97,99,102,106 Unpublished literature was not considered for inclusion in this review, leading to potential selection bias. Further bias may have also been introduced via the decision to limit studies to English-language studies only.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The project group obtained considerable experience in developing lifestyle interventions aiming at preventing T2D in high-risk individuals [73]. The DE-PLAN project has also formed a basis for the IMAGE project that is currently developing the European guideline for the prevention of T2D [74]. …”
Section: Primary Prevention Of Type 2 Diabetes Mellitusmentioning
confidence: 99%